NowościThe role and importance of protection and thrombectomy devices during percutaneous coronary interventions in degenerated vein grafts - Tajstra, Mateusz; Hawranek, Michał; Gąsior, Mariusz (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Percutaneous coronary interventions (PCI) in degenerated saphenous vein grafts (SVG) often lead to distal embolization with thromboembolic debris. This may lead to serious adverse complications such as myocardial infarction. The most often used distal and proximal protection devices as well as thrombectomy devices are presented with their usefulness in different clinical settings.